2001
DOI: 10.2466/pms.2001.92.3.682
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Assessment of Battered Women: A Pilot Study

Abstract: Mean performance of 19 battered women was significantly lower than that of 9 control women on the Halstead-Reitan Neuropsychological Battery, the Wechsler Memory Scale-Revised, and the Quick Neurological Screening Test. 58% of the battered women scored in the impaired range on the Halstead-Reitan Impairment Index; and 53% scored in the impaired range on the Quick Neurological Screening Test. More definitive research was recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
(1 reference statement)
0
4
0
1
Order By: Relevance
“…Previous studies from other countries also confirm that head injuries are a significant concern for women. Various types of head injuries can result in traumatic brain injury and neurological damage and disorganization (Deering, Templer, Keller & Canfiled, 2001;Muelleman, Lenaghan & Pakeser, 1996).…”
Section: Consequences To the Victimsmentioning
confidence: 99%
“…Previous studies from other countries also confirm that head injuries are a significant concern for women. Various types of head injuries can result in traumatic brain injury and neurological damage and disorganization (Deering, Templer, Keller & Canfiled, 2001;Muelleman, Lenaghan & Pakeser, 1996).…”
Section: Consequences To the Victimsmentioning
confidence: 99%
“…It is estimated that approximately 50% of women exposed to IPV suffer multiple brain injuries due to abuserelated head trauma (Valera, 2018;Valera & Berenbaum, 2003). Another study of individuals experiencing IPV reported on average >200 assaults with blows to the head per individual (Deering, Templer, Keller, & Canfield, 2001). However, this number only captures the incidents with at least one blow to the head and does not reflect the frequency of hits during a single assault, which is likely higher (Deering et al, 2001).…”
Section: Tbi History: Head Trauma In Individuals Who Have Experiencedmentioning
confidence: 99%
“…Another study of individuals experiencing IPV reported on average >200 assaults with blows to the head per individual (Deering, Templer, Keller, & Canfield, 2001). However, this number only captures the incidents with at least one blow to the head and does not reflect the frequency of hits during a single assault, which is likely higher (Deering et al, 2001). Thus, future research needs to account for the high likelihood of exposure to repetitive head trauma in this population.…”
Section: Tbi History: Head Trauma In Individuals Who Have Experiencedmentioning
confidence: 99%
“…Furthermore, it is novel in its inclusion of a diverse sample of women. To date, the majority of research on neuropsychological performance in IPV survivors has been conducted in North America (Aupperle et al, 2016;Deering et al, 2001;Hebenstreit et al, 2014;Muir et al, 2022;Raskin et al, 2023;Seedat et al, 2005;Stein et al, 2002;Twamley et al, 2009;Valera & Berenbaum, 2003;Valera & Kucyi, 2017;. To the best of our knowledge, only four studies have examined neuropsychological functioning among IPV survivors outside of this geographical region (Castro et al, 2022;Chung et al, 2014;Daugherty et al, 2019;Rodriguez & Guzmán Cortés, 2023), thus limiting the representativeness of our understanding of the potential impact of IPV on cognition in diverse samples.…”
Section: Introductionmentioning
confidence: 99%